A SPEECH ACT ANALYSIS OF DIRECT UTTERANCES ON SHORT STORY THE LOST “BEAUTIFULNESS”IN ORDER TO UNDERSTAND COMMUNICATION TOWARD LANGUAGE - Satiul Komariah (Proceedings Education and Language International Conference, 2017)
This research aimed to investigate: (1) the form of direct sentences on short story entitled The Lost “Beautifulness”, (2) analyzing the purpose of the direct utterances in the short story in order to understand the communication toward language, (3) show the kind of direct utterances as a part of language utterances in short story The Lost “Beautifulness”. The object used in this research are direct utterances which is smallest unit of speech on short story The Lost “Beautifulness”. The data were collected by observation method. The writer selecting the direct utterances which can be found in the short story. The results of the research showed that: (1) form of the direct utterances are divided into three; declarative, interrogative and imperative sentence; (2) purposes of the utterances depend on the four factors; locution, illocution, perlocution and social context; (3) kinds of speech acts are divided into 7: assertive, performative, verdictive, expressive, directive, commisive and phatic utterances.Keywords: Speech act, Direct Utterance, Short Story